Hubungan Indeks Massa Tubuh (Imt) Terhadap Tekanan Darah Pada Pasien Program Rujuk Balik (PRB) Hipertensi Di Puskesmas Somagede Banyumas - Purnomo Ardi Wibowo; Mariah Ulfah; Madyo Maryoto (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aimed to analyze the relationship between body mass index (BMI) and blood pressure among patients enrolled in the hypertension referral-back program at Somagede Primary Health Center, Banyumas. A quantitative cross-sectional design was applied involving 142 respondents selected through purposive sampling from a population of 220 patients. Data were obtained from secondary clinical records and analyzed using chi-square tests and contingency coefficient analysis. The findings demonstrated a statistically significant association between BMI and blood pressure (p = 0.001), with a moderate positive correlation (cc = 0.399). The distribution indicated that individuals with higher BMI categories, particularly overweight and obese groups, exhibited greater proportions of elevated blood pressure levels, including stage I and stage II hypertension. These results support the role of BMI as an important clinical indicator in assessing hypertension severity. However, the moderate strength of association suggests the involvement of additional contributing factors. Integrating weight management strategies into primary healthcare interventions may enhance blood pressure control among hypertensive patients in community-based programs.